Diseño de un plan de mantenimiento preventivo para la planta de lácteos y el centro de biotecnología de la quinta experimental punzara en la Universidad Nacional de Loja mediante la aplicación del software MP. - Díaz Chamba, Diego Orlando (2015)
The following tesis work arises like principal objective the elaboration of a maintenance plan for the Planta de Lácteos and the Centro de Biotecnología of the Quinta Experimental Punzara, this Project have the purpose to be an instrument for the conservation of the equipment that are located in the installations listed above. Actually the installations don´t have a function maintenance plan which allows to have information about maintenance interventions in equipment and technical information from them. In base above background, the project plans a methodology which is based in three stages: analysis of the installations, determining the guidelines of the maintenance plan and maintenance planning. The methodology have diferents themes and relevant concepts in the development of the maintenance plan such as criticality analysis, Pareto analysis, cause-effect analysis, among others. All the analized aspescts allows for result a data base analized technically, with proper planning of maintenance activities relevant to each equipment, and the asignation of nescesary resources for the activities realization. The information will be the basis for future studies. The project finally considers the development of an alternative approach to management through the implementation of a Computerized Maintenance Management System (CMMS) allowing easy management activities, execution and supervision under planning.